Aborcja i eutanazja jako anty-ekologiczne „uderzenia” w małżeństwo i rodzinę - Sakowicz, Eugeniusz (Studia Pastoralne, 2020)
Matrimony and family having a sacral status in every religion and being a sacrament in Christianity, are under attack from totalitarian systems which are both openly aggressive, driven by hatred. Nowadays the world is a witness to a fervent dispute concerning matrimony and family. These institutions acting as the guardians of the moral order and harmony experience numerous ‘attacks’. Their aim is desecration and the ultimate annihilation of the abovementioned institutions. A particularly brutal attack – ‘blow’ aimed at the family is abortion and euthanasia. They are actions “sponsored” by worldwide corporations of hatred towards human beings. Although they are passed by parliaments as the greatest achievements of democracy, they are in fact its denial. They express violence towards nature, environment, God’s order inscribed into this world. In the light of these arguments they are theoretically and practically anti-ecological. Death of aborted human beings, as well as senile, mentally or terminally ill people submitted to euthanasia, is an expression of a totalitarian ideology which always despises one group and glorifies the other. It labels some people as subhumans and others as superhumans. Both these acts of violence, which are in fact an illegal death penalty imposed on the innocent, ultimately strike matrimony and family as institutions deemed as sanctified by the Catholic Church and ordained by God. The modern matrimony and family willing to ‘be themselves’ have to fight in order to keep their identity. It can be done by a decisive resistance towards any “strikes”. By these actions matrimony and family shall fulfil the culture-making mission first in the matrimonial and family circle, next in the society and finally in the nation. The family has always been ”the communion of people” and wants to retain its status. It is within the family where the biggest and the most precious human effort is taken – the task of raising children in the context of matrimonial and family love, the effort of maturating towards eternity and salvation. Only if the family and matrimony are strong in God, can they survive the sinister anti-ecological “strike” coming from the policy propagating abortion and euthanasia.